2015
DOI: 10.1111/jopr.12366
|View full text |Cite
|
Sign up to set email alerts
|

Six‐Year Survival of a Mini Dental Implant‐Retained Overdenture in a Child with Ectodermal Dysplasia

Abstract: Patients with ectodermal dysplasia (ED) experience several problems caused by abnormal development and functioning of the head and neck region. In addition to developmental nasal cartilage abnormalities and absence of sweat glands, hair, and eyebrows, edentulism or developmental disorders of teeth (cone-shaped teeth) are commonly observed in these types of patients. ED is also characterized by underdeveloped alveolar ridges, a decreased occlusal vertical dimension, reduced salivary secretion, and dry oral muco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 23 publications
(37 reference statements)
0
14
0
4
Order By: Relevance
“…Replacing the lost soft and hard tissues and restoring the missing teeth are the main goals in the treatment of ED patients to achieve a proper vertical dimension and facial soft tissue appearance. (17) Despite severe bone deficiencies, implant rehabilitation can be a good solution for ED patients. Several methods have been introduced for alveolar bone augmentation, including autogenous, allogenic, and xenogeneic bone grafts, vertical distraction osteogenesis (DO), sinus floor augmentation, and the combination of the mentioned modalities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Replacing the lost soft and hard tissues and restoring the missing teeth are the main goals in the treatment of ED patients to achieve a proper vertical dimension and facial soft tissue appearance. (17) Despite severe bone deficiencies, implant rehabilitation can be a good solution for ED patients. Several methods have been introduced for alveolar bone augmentation, including autogenous, allogenic, and xenogeneic bone grafts, vertical distraction osteogenesis (DO), sinus floor augmentation, and the combination of the mentioned modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Several methods have been introduced for alveolar bone augmentation, including autogenous, allogenic, and xenogeneic bone grafts, vertical distraction osteogenesis (DO), sinus floor augmentation, and the combination of the mentioned modalities. (2,17,18) Kilic et al reported that dental implant insertions in association with guided bone regeneration would be a successful treatment in ED patients. (17) However, unpredictable resorption of the bone graft and delayed placement of implants are among the disadvantages of the abovementioned procedure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3 Kalıtsal bir hastalık olan ektodermal displazi (ED) de anodonti veya oligodonti ile karakterizedir. [4][5][6] Bu gibi durumlarda estetik, fonasyon ve fonksiyon sağlamak amacıyla iskeletsel ve dental gelişim tamamlanmadan önce oral rehabilitasyona ihtiyaç duyulmaktadır.…”
unclassified